Understanding Metabolic Syndrome: Causes and Prevention : A Literature Review - Nur Firdausiyah, Shofie Ayu; Devi, Debrina Kusuma (Journal of Diverse Medical Research: Medicosphere, 2025)
Metabolic syndrome is a health condition involving interrelated metabolic disorders, increasing the risk of cardiovascular disease and type 2 diabetes. This condition involves central obesity, high triglyceride levels, low HDL cholesterol, hypertension, and high blood sugar levels. The increasing prevalence of metabolic syndrome in Indonesia is mainly caused by lifestyle changes, including unhealthy eating patterns and low physical activity. This research aims to identify causal factors and prevent metabolic syndrome. Literature studies were used to analyze the epidemiology, risk factors, and prevention strategies for metabolic syndrome. Prevention of this syndrome requires a comprehensive approach, including healthy lifestyle changes, such as a balanced diet, physical activity, and stress management. Modern technology and public policies that support healthy lifestyles can also strengthen these prevention efforts. With proper prevention, the risk of chronic diseases related to metabolic syndrome can be reduced, as well as improving people's quality of life.